On the Lie symmetries of the boundary value problems for differential and difference sine-Gordon equations - Yildirim, O.; Caglak, S. (KARAGANDA STATE UNIV, 2021)
In general, due to the nature of the Lie group theory, symmetry analysis is applied to single equations rather than boundary value problems. In this paper boundary value problems for the sine-Gordon equations under the group of Lie point symmetries are obtained in both differential and difference forms. The invariance conditions for the boundary value problems and their solutions are obtained. The invariant discretization of the difference problem corresponding to the boundary value problem for sine-Gordon equation is studied. In the differential case an unbounded domain is considered and in the difference case a lattice with points lying in the plane and stretching in all directions with no boundaries is considered.
Keywords: symmetry analysis; partial differential equations; difference equations; boundary value problems; Mathematics